2016
DOI: 10.1016/j.taap.2016.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Systemic metabolic derangement, pulmonary effects, and insulin insufficiency following subchronic ozone exposure in rats

Abstract: Acute ozone exposure induces a classical stress response with elevated circulating stress hormones along with changes in glucose, protein and lipid metabolism in rats, with similar alterations in ozone-exposed humans. These stress-mediated changes over time have been linked to insulin resistance. We hypothesized that acute ozone-induced stress response and metabolic impairment would persist during subchronic episodic exposure and induce peripheral insulin resistance. Male Wistar Kyoto rats were exposed to air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 62 publications
1
58
0
Order By: Relevance
“…Serum lipids and metabolic hormones were assessed since exercise training can affect these measures and acute ozone exposure has been shown to affect serum metabolites in rats and humans (24,25). Insulin levels were similar between active and sedentary rats and were not affected by ozone exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum lipids and metabolic hormones were assessed since exercise training can affect these measures and acute ozone exposure has been shown to affect serum metabolites in rats and humans (24,25). Insulin levels were similar between active and sedentary rats and were not affected by ozone exposure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This would indicate a deleterious interaction between seden- tary lifestyle and ozone exposure. It has been shown that ozone, through activation of the sympathetic nervous system and the hypothalamic-pituitary-adrenal axis, increases circulating stress hormones, leading to increased liver gluconeogenesis and inhibition of insulin secretion by the pancreas resulting in hyperglycemia and glucose intolerance (24,25). Following exposure to relatively high concentrations of ozone (1.0 ppm), rats are hyperglycemic and show impaired glucose tolerance as compared with rats exposed to filtered air.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of maternal HFD on ozone-induced lung injury/inflammation, and circulating hormones and lipids. Ozone exposure has been shown to induce lung injury and inflammation in many of our rat studies 25,31 , which begins to occur immediately-post exposure but peaks next day 23,31 . To determine lung injury in male and female offspring immediately after a single 5 h ozone exposure, we assessed BALF injury markers and neutrophilic inflammation.…”
Section: Body Weights and Body Fat Composition Of Dams And Offspringmentioning
confidence: 92%
“…We further proposed that these metabolic alterations in the offspring induced by maternal high fat diet will be exacerbated after exposure to an environmental stressor, ozone. This was based on our recent findings that exposure to air pollutants, such as ozone and acrolein, induces a wide array of systemic metabolic changes in rodents [22][23][24][25][26] and in humans 27 through the activation of neuroendocrine stress pathways involving the sympathetic-adrenal-medullary and hypothalamic-pituitary-adrenal axes 10,28 . We hypothesized that offspring born to obese mothers on HFD when challenged with such an environmental stressor, will produce exacerbated metabolic alterations which will unmask the susceptibility in offspring to metabolic impairment and reveal maternal contribution to childhood metabolic disease.…”
Section: Ghmentioning
confidence: 99%
“…Among the environmental hazardous factors known to cause adverse effects on health, ozone (O 3 ) is a major factor in air pollution, which is widely recognized as a particularly harmful risk to airway health ( 7 , 8 ). In human and animal studies, it has been demonstrated that early exposure at post-natal stage or long-term exposure at later stages to O 3 may result in pathological changes in the respiratory system, including modifications of time and mode of alveolar growth and development ( 9 , 10 ). It has been reported that O 3 exposure may also cause inflammation in the airways and the lungs and structural reorganization of smooth muscle cells ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%